2010
DOI: 10.1007/s11664-010-1150-3
|View full text |Cite
|
Sign up to set email alerts
|

Eutectic Microstructure and Thermoelectric Properties of Mg2Sn

Abstract: Ingots of undoped and Ag-doped Mg 2 Sn were prepared from the melt using a rocking Bridgman furnace at different cooling rates: slow cooling (0.1 K/min), moderate cooling (1 K/min), and rapid quenching. The ingots show very different microstructure and thermoelectric properties. Slow-cooled ingots consist of large Mg 2 Sn crystals with minor inclusions. Moderate-cooled ingots show significant variation in composition and microstructure, with Mg-rich material at the topmost section of the ingot and Sn-rich mate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
6
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(8 citation statements)
references
References 19 publications
2
6
0
Order By: Relevance
“…4(a). These values are comparable with those reported for the bulk single crystal, 11,16,31 suggesting high quality of our thin films. In the literature, Mg-based II-IV semiconductor thin films have been reported to have lower values than the bulk material.…”
supporting
confidence: 91%
“…4(a). These values are comparable with those reported for the bulk single crystal, 11,16,31 suggesting high quality of our thin films. In the literature, Mg-based II-IV semiconductor thin films have been reported to have lower values than the bulk material.…”
supporting
confidence: 91%
“…Although to achieve p-type doping the silver atom must be incorporated at substitution sites, it appears some silver reacts with Mg to form finely dispersed MgAg eutectic clusters and/or MgAg precipitates at lower Ag-content (images c, d) or fine interconnected MgAg threads at the highest silver content (image e). By contrast the ingots grown by the Bridgman method at different cooling rates showed significant variation in composition and microstructure [16]. The Bridgman samples BR1-BR5, which were prepared at a very slow growth rate (0.1 mm/min), are less uniform in microstructure as compared with the RF samples.…”
Section: Microstructurementioning
confidence: 91%
“…Recently we reported on the preparation and properties of single and large-grain polycrystalline Mg 2 Sn thermoelectric materials prepared by the Bridgman method [8,9,16,17]. Here, we report on the preparation of Mg 2 Sn ingots doped with Ag (0-1 at%) prepared by the RF induction melting.…”
Section: Introductionmentioning
confidence: 99%
“…In the present study, we focus on Mg 2 Sn with the same crystal structure as Mg 2 Si. Mg 2 Sn has been studied extensively as a potential TE material [18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37] . Xin et al 31 reported that an Sb-doped n-type polycrystalline Mg 2 Sn, Mg 2.15 Sn 0.98 Sb 0.02 exhibited a zT value of 0.53 at 650 K (κ and PF are 4.7 W/mK and 3.9 W/mK 2 , respectively).…”
mentioning
confidence: 99%
“…Regarding the TE properties of pristine Mg 2 Sn, single crystals exhibited different S values depending on the preparation method, as shown in Table 1 [18][19][20][21][22][23] . Generally, different S values reflect differences in carrier concentration.…”
mentioning
confidence: 99%